Faktor-Faktor yang Mempengaruhi Niat Menggunakan Aplikasi Access by KAI di Kota Bogor - Rizki Syaban Mulyasaputra; Ryna Parlyna; Osly Usman (Indo Publishing, 2026)
This study aims to analyze the influence of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Perceived Behavioral Control (PBC), and Attitude Toward (ATT) on the Behavior Intention to Use (BIU) the Access by KAI application in Bogor City. A quantitative approach was applied using the PLS-SEM method via SmartPLS software. Through a purposive sampling technique, a sample of 130 respondents aged 17-42 years who were familiar with and had used the application 1 to 2 times was obtained. The research data was collected using a structured questionnaire instrument consisting of 26 statement items. The results show that PU, PEOU, and ATT have a positive and significant influence on BIU. Conversely, PBC was found to have no positive influence on BIU. In the mediation test, ATT successfully mediated the influence of PU on BIU, but failed to mediate the influence of PEOU on BIU. Furthermore, PU did not significantly mediate the influence of PEOU on BIU. These findings indicate that user intentions to utilize the Access by KAI application are more dominantly influenced by perceived benefits, ease of use, and positive attitudes compared to perceived behavioral control. The strongest relationship is shown by the influence of PEOU on PU with a coefficient of 0.790, t-statistics 13.123, and p-value 0.000.